Dietary variation in diabetics. - Hackett, A F (1988)
The day to day variation in the energy and carbohydrate intake of 168 children with diabetes on Tyneside and Teesside was less than that of 405 non-diabetic children. It was, however, still considerable, the average range of carbohydrate intake over three days being 51 g. The variation in carbohydrate intake was not related to diabetic control nor to the families' knowledge of diabetes. Compliance with the dietary prescription deteriorated during the day. These findings support a qualitative approach to the dietary prescriptions for diabetics.